Factibilidad para la creación de una empresa de servicios de limpieza para instituciones públicas y privadas en el cantón Buena Fe, año 2015 - Cedeño Loor, Carlos Andrés (2015)
This research aims to conduct a feasibility study for the establishment of a company of cleaning services for public and private institutions in Buena Fe city. In order to elaborate this project, it was developed a market survey and analysis of demand and supply. Also, a technical study was develop to show the requirements for the creation of the company and a financial study which show the economic viability of this project. The methods used in this research have been inductive, deductive, and analytic which were applied through a survey to managers of private and public institutions of the canton before mentioned. Among the conclusions obtained in this research it can be detailed: In the market study found that there is a potential demand of 61% and an offer of 0%. This factor should be considered positive because it is an indication that the creating a cleaning services company said demand will be met and thus generate income. The technical study necessary features were established to carry out the operations of the company for which it is considered that the installed capacity for a company of cleaning services in Buena Fe city must be 52 companies and it is estimated that by the end the project it would be using 79% of its installed capacity. As for the optimal location this would be on Mariana Rodriguez and Victor Juez streets in Buena Fe city, due to its central location. Finally in the financial study it is determined that the creation of this company is feasible because it has a 39.85% IRR, NPV of $ 27,109.56 USD and a relation benefit cost (B / C) that for every dollar invested a profit of $ 0.10 USD will, in addition to the invested capital would be recovered over a period of 2 years, 10 months and 27 days. Keywords: Market Research, Feasibility, Company of Cleaning Services.